(3EOGQI GdeSJKajGJ hGdeQGcR GdUMjI GdMOjKI (B:s (3efXhQ TGed (B/s - (3PjGH, UdGM eMeOs ((3YeGf(B: s (3OGQ GdacQ(B, s, 2009)
(3eaghe h JWhQ GdGOGQI GdUMjI GdfXGe GdUMj h GdJNWjW GdUMj , GdJfXje h Gdgjcd GdJfXjej aj GdeSJTajGJ h GdeQGcR GdUMjI , EOGQI Gdbhi GdHTQjI hGdQbGHI aj GdeSJTai h GdeDSSGJ GdUMjI GdhXGFa h GdegGe ddGbSGe h GdhMOGJ GdJfXjejI I Jbjje GdGOGA aj GdeSJTajGJ , EOGQI GdUQGY aj GdeSJTais
Keywords: (3GdUMI GdYGeIs; (3GdeSJTajGJ `` GOGQIs; (3GdeTJTajGJs